2013
DOI: 10.1128/iai.00278-13
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus reuteri Attenuates the Stressor-Enhanced Severity of Citrobacter rodentium Infection

Abstract: dStressor exposure has been shown to enhance host susceptibility and the severity of a plethora of illnesses, including gastrointestinal disease. In mice, susceptibility to Citrobacter rodentium has been shown to be dependent on host genetics as well as the composition of the intestinal microbiota, but the effects of stressor exposure on this gastrointestinal pathogen have not been elucidated fully. Previously, our lab showed that exposure to the prolonged-restraint stressor prior to a challenge with C. rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…[46][47][48][49] Additionally, treatment with probiotic Lactobacillus reuteri in mice abrogates the stressor-induced increases in the severity of the inflammatory response to a colonic pathogen. 40 Interestingly, though previous studies have found that Lactobacillus is reduced in the stool, 18,20,21,50 this study showed a reduction in mucosal epithelium-associated Lactobacillus but not in luminal lactobacilli, implying that psychological stressor exposure can have a distinct effects upon groups of mucosal microbiota compared to their luminal counterparts. Since Lactobacillus and other commensals can mediate host gut health, this specific reduction might be associated with stressor-induced increases in colitic inflammation.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…[46][47][48][49] Additionally, treatment with probiotic Lactobacillus reuteri in mice abrogates the stressor-induced increases in the severity of the inflammatory response to a colonic pathogen. 40 Interestingly, though previous studies have found that Lactobacillus is reduced in the stool, 18,20,21,50 this study showed a reduction in mucosal epithelium-associated Lactobacillus but not in luminal lactobacilli, implying that psychological stressor exposure can have a distinct effects upon groups of mucosal microbiota compared to their luminal counterparts. Since Lactobacillus and other commensals can mediate host gut health, this specific reduction might be associated with stressor-induced increases in colitic inflammation.…”
Section: Discussionmentioning
confidence: 44%
“…22,40 It is not known whether stressorinduced changes to the microbiota were solely responsible for the increased disease severity, but orally treating the mice with probiotic L. reuteri reduced the severity of C. rodentium infection in stressor-exposed mice, 40 suggesting that preventing stressorinduced reductions in lactobacilli might attenuate colonic inflammation. However, the effects may not be specific to lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Soc. B 371: 20150122 and cytokines into circulation [153][154][155][156][157][158]. Interestingly, these physiological responses and the composition of microbial communities return to baseline following cessation of stressors, suggesting increased resilience to environmental challenges during adulthood [159].…”
Section: (D) Adulthood and Agingmentioning
confidence: 99%
“…Because multiple studies demonstrated that stressor exposure consistently reduces the relative abundance of bacteria in the genus Lactobacillus, and because the lactobacilli are known to have immunomodulatory functions 37,38,39 , studies from this laboratory have been focused on determining whether the lactobacilli are involved in stressor-induced immunomodulation.…”
Section: Biological Functions Of Microbiota During Stressor Exposurementioning
confidence: 99%